Intra-Articular Vancomycin Powder Eliminates Methicillin-Resistant S. aureus in a Rat Model of a Contaminated Intra-Articular Implant. (1st February 2017) - Edelstein, Adam I.; Weiner, Joseph A.; Cook, Ralph W.; Chun, Danielle S.; Monroe, Emily; Mitchell, Sean M.; Kannan, Abhishek; Hsu, Wellington K.; Stulberg, S. David; Hsu, Erin L.
Abstract : Background: Periprosthetic joint infection following hip and knee arthroplasty leads to poor outcomes and exorbitant costs. Topical vancomycin powder has been shown to decrease infection in many procedures such as spine surgery. The role of vancomycin powder in the setting of total joint arthroplasty remains undefined. Our aim was to evaluate the efficacy of intra-articular vancomycin powder in preventing infection in a rat model of a contaminated intra-articular implant. Methods: Thirty-two female Sprague-Dawley rats underwent knee arthrotomy and implantation of a femoral intramedullary wire with 1 mm of intra-articular communication. The knee joint was also inoculated with 1.5 × 10 7 colony forming units (CFU)/mL of methicillin-resistant Staphylococcus aureus (MRSA). Four treatment groups were studied: (1) no antibiotics (control), (2) preoperative systemic vancomycin, (3) intra-articular vancomycin powder, and (4) both systemic vancomycin and intra-articular vancomycin powder. The animals were killed on postoperative day 6, and distal femoral bone, joint capsule, and the implanted wire were harvested for bacteriologic analysis. Statistical analyses were performed using Wilcoxon rank sum and Fisher exact tests. Results: There were no postoperative deaths, wound complications, signs of vancomycin-related toxicity, or signs of systemic illness in any of the treatment groups. There were significantly fewer positive cultures in the group that received vancomycin powder in combination with systemic vancomycin compared with the group that received systemic vancomycin alone (bone: 0% versus 75% of 8, p = 0.007; Kirschner wire: 0% versus 63% of 8, p = 0.026; whole animal: 0% versus 88% of 8, p = 0.01). Only animals that received both vancomycin powder and systemic vancomycin showed evidence of complete elimination of bacterial contamination. Conclusions: In a rat model of a contaminated intra-articular implant, use of intra-articular vancomycin powder in combination with systemic vancomycin completely eliminated MRSA bacterial contamination. Animals treated with systemic vancomycin alone had persistent MRSA contamination. Clinical Relevance: This animal study presents data suggesting that the use of intra-articular vancomycin powder for reducing the risk of periprosthetic joint infections should be investigated further in clinical studies.